Eksplorasi dan Identifikasi Jamur Penyebab Bercak Daun pada Bibit Kelapa Sawit di Main Nursery Perkebunan Rakyat Kabupaten Deli Serdang - Manurung, Sanju; Dibisono, Mhd Yusuf; Nurliana, Nurliana (Lembaga Teewan Journal Solutions, 2026)
Leaf spot disease is one of the major diseases affecting oil palm (Elaeis guineensis Jacq.) seedlings during the nursery stage and may reduce seedling quality. This study aimed to explore and identify fungal pathogens associated with leaf spot disease and to determine disease intensity in community-owned oil palm main nurseries in Deli Serdang Regency. The research used a survey method with a quantitative descriptive approach. Samples were collected from nurseries in Percut Sei Tuan, Pagar Merbau, and Galang districts. Fungal identification was carried out through isolation on Potato Dextrose Agar (PDA) medium followed by macroscopic and microscopic observations. The observed variables included fungal species, disease incidence, and disease intensity. The results showed that the fungi associated with leaf spot disease were Curvularia sp. and Pestalotiopsis sp. Curvularia sp. was the dominant fungus, representing 73.68% of the isolates, while Pestalotiopsis sp. accounted for 26.32%. Symptoms observed on infected leaves included brown to black lesions that developed into necrotic spots. The average disease intensity was 13.47%, categorized as low. The highest intensity occurred in Percut Sei Tuan (17.06%), followed by Pagar Merbau (12.84%) and Galang (10.52%). Environmental conditions, especially humidity and sanitation, influenced disease development. Improved sanitation, proper seedling spacing, and regular monitoring are recommended to reduce disease incidence and maintain seedling quality.